Nature, spirituality, and early childhood education : fostering children's awareness and responsibility through outdoor learning - Wills, Ruth (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This novel volume delves into a specific and crucial aspect of early years pedagogy - the intersection between early childhood education and spirituality, offering tips on nurturing spirituality and a sense of connectedness with nature through outdoor learning. With experience both as a scholar and a teacher, the author delves into the ontological and epistemological issues related to outdoor learning and education while keeping accessibility and sustainability at the centre of the volume. Chapters take a comprehensive approach to the exploration of children's innate spirituality and their connection with nature in the context of early childhood education, fusing elements such as a critique of early years policy with philosophy of education and children's mental health. Using a robust theoretical foundation incorporating philosophical figures such as Froebel, McMillan, Montessori, Dewey and Freire, as well as the inclusion of practical examples from educational settings designed for real-world scenarios, this book reinvigorates the conversation around the holistic development of children by emphasizing the importance of nature and child-centred pedagogies. Ultimately exploring avenues that can foster a sense of well-being and social responsibility in children, the book will be of interest to researchers, educators and teacher trainers in the field of early childhood education, environmental education, philosophy of education and teacher education. Policy makers and school leaders may also benefit from this volume"--
Preamble : children's spirituality in the outdoor space : seven vignettes -- Children's spirituality, nature and early childhood policy -- Children's spirituality, nature and frameworks of understanding -- Children's spirituality, nature and early childhood foundations -- Children's spirituality, nature and early childhood practice -- Children's spirituality, nature and pedagogy -- Children's spirituality and nature : recommendations for policy and practice.
Keywords: Early childhood education -- Psychological aspects; Nature study; Spirituality -- Study and teaching (Early childhood); EDUCATION / General; EDUCATION / Non-Formal Education; EDUCATION / Philosophy & Social Aspects